Religious Counseling With A Cultural Approach "Basasandi Syarak, Syarak Basandi Kitabullah" to Improve Islamic Spiritualism - Syafitri, Reri; Zubaidah, Zubaidah; Carol, Tuomi; Steven, Gooding (International Journal of Research in Counseling, 2022)
Counseling is an activity to help the counselee so that his daily life becomes an effective life. The current phenomenon that occurs in the West Sumatra region is the occurrence of moral decadence caused by many things and one of the causes is that people no longer apply "adat basandi syarak, syarak basandi Kitabullah". The method used in this study is the library research method or a method that explores articles or research that discusses the things the researchers are researching. The results of religious counseling research with the cultural approach of "adat basandi syarak, syarak basandi Kitabullah" are effective in helping counselee problems.